Could educational reforms have something to do with Mundell's triangle of impossibility? - Deer, C; de Meulemeester, J (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2004)
In this paper we discuss the role given to education and training by policy-makers in France and Britain between 1980 and 2000 in relation to their chosen socio-economic strategies. We highlight conjunctions between levels of economic openness, exchange rate environments and types of educational policies. The two countries are interesting case studies due to the high degree of time-consistency between the policies implemented by stable governments (albeit of opposite political orientations). In Britain, a strategy of deregulated labour markets, a scaled-down welfare state, reduced taxation and monetarist rules against inflation was implemented whilst exchange rates floated for most of the period. Educational policy appeared initially to be part of an ideological package but became a prominent concern ‘of its own’ during periods of semifixed exchange rates (1987-92) and when the value of the pound soared (from 1997 onwards). This indicates that human capital policies as a strategy for increasing the overall competitiveness of a nation may be influenced by the exchange rate environment and the general political economic context. This idea is further strengthened by the case of France, where, after a short-lived attempt between 1981 and 1983 at reflating the economy via Keynesian-informed principles, French policy-makers chose to take the route of European integration with exchange rates fixed at a high level. In a rigid labour market and with public policies positively restricting the possibilities of further deregulation and tax reductions, unemployment levels soared, especially among young people. These elements may explain the increased emphasis placed on education and training for boosting competitiveness from a human capital perspective in the hope that this would foster quality and innovation so as to maintain and improve the country’s competitiveness in an increasingly open economy and integrated European Union.